Correlation between failures causes, quality indices and forging technology of products for metallurgical equipment and transport - Василевский, О.В.; Кухарь, В.В. (Problems of Tribology, 2016)
Vasylevskyi O.V., Kukhar V.V. Correlation between failures causes, quality indices and forging technology of products for metallurgical equipment and transport.Indices for characteristic of quality of products for the metallurgical equipment and transport that produced by forging were analyzed. Correlation between the quality indices of forged parts and durability of work-parts that made of such forgings is shown. The numbers of experimental and industrial research were made in terms of press-forging shop of LLC "Metinvest – Mariupol Mechanical Repair Plant" that allowed to determine the effect of the mechanical properties, macrostructure and microstructure, obtained by forging used modes, on the performance characteristics of forged parts. Investigations were carried out with respect to products manufactured from steel 25X1M1Ф, 40ХН2MA and Steel 45 grades on the hydraulic forging press DP1141A1 model with 12.5MN nominal strength. Spectral method for determining the chemical composition of steel, ultrasonic inspection method, metallographic methods for determining segregation sulfuric fingerprint, macrostructure and microstructure, standardized methods of mechanical tests used to analyze. In addition to research directly to fractures and destruction of places, devoted considerable attention to technological and thermomechanical modes under which were to forge defective products. Executed generalization of breakdowns (failures) causes "Mouthpiece", "Dorn 12 '", "Roller", "Axis" parts has allowed to determine that the main direction of increasing the resistance of the details of metallurgical equipment and transport is the development of modes of forging that providing the uniformity of the accumulated deformation (local working of cast metal), and the uniformity of the microstructure, generally uniform of mechanical properties in the parts’ cross sections. Keywords: forged products, forging mode, reducing of square, quality indices, microstructure, failure cause, method of quality control.